A study on traffic congestion in Kota Bharu, Kelantan - Lee, Zhu Ming; Lee, Qin; Mohd Basri, NurAisha; Khosim, Siti Maisaroh (2015)
The purpose of this study is to investigate the factors that cause traffic congestion in Kota Bharu as well as to examine the possible solutions to reduce traffic congestion in Kota Bharu. Major growth of traffic volume in Kota Bharu shows that Kota Bharu is facing traffic congestion on its urban roads due to the rapidly changes in the structure of Kota Bharu city, as well as the growing population demand on vehicles that effect on difficulties to manage traffic flow had increased from day to day.Poor driving habits, poor road management and lack of public transport facilities are the most factors that cause traffic congestion.Then, a study on factors of traffic congestion was conducted by collecting the data by using survey method by a structured questionnaire with close-ended question that distributed to 400 respondents of publics in Kota Bharu. So, methods that were used to analyze the data are reliability analysis, descriptive analysis and Pearson Correlation Coefficient analysis to know which factors those more influence on traffic congestion in Kota Bharu. The result shows that all factors have relationship on traffic congestion in Kota Bharu but poor driving habits and poor road management are mostly cause traffic congestion in Kota Bharu and following by lack of public transport facilities that rated at the lowest mean. Based on this study, most of solutions that highly chosen by publics to reduce traffic congestion in Kota Bharu are enforcement the traffic laws, increase road capacity and improve the quality of road maintenance and repair. Infrastructure and population of city also should be emphasized for future study to more understand about traffic congestion